A life cycle perspective on land use and project economics of electricity from wind and anaerobic digestion. (February 2016) - Ciliberti, Carlo; Jordaan, Sarah M.; Smith, Stephen V.; Spatari, Sabrina
Abstract: Feed-in tariffs and Renewable Portfolio Standards (RPS) are among the most prominent policies to address anthropogenic influence on climate change. Implementation of RPS favorably affects renewable energy supply and rural development while reducing the land available for meeting demand for food and feed resulting from global population growth. Even in the vast Great Plains of the United States, land requirements are primary considerations between increasing renewable energy capacity and food and feed production. This study applied life cycle assessment (LCA) and project economics to estimate and compare the land intensity and profitability of anaerobic digestion and wind energy projects in the Great Plains. The results show that significantly more energy and revenue can be generated per hectare of land using wind versus anaerobic digestion. Economically, the benefit-to-cost ratios of wind farms were almost twice as favorable as anaerobic digester facilities. Wind farms have consistent benefit-to-cost ratios of 2.15 while the anaerobic digester facilities benefit to cost ratios range from 1.2 to 1.25. Legislature changes to RPS could incentivize increasing the number of anaerobic digesters while also assisting in reversing the current trend of diminishing dairy farms while reducing climate change risks and creating new economic opportunities for renewable energy. Highlights: Wind 1160 GW h to 28, 706 GW h between 2 and 129 ha. AD 29 GW h to 393 GW h between 14 and 105 ha. More energy and revenue can be generated per hectare using wind energy AD. An ideal solution for dairy farmers may be an integrated solution State legislature changes to RPS could incentivize increasing AD facilities.